Kohärenzgefühl und Religiosität bei polnischen und deutschen Studierenden - Malgorzata Schonder (International Dialogues on Education: Past and Present, 2017)
This empirical study contributes to the question of whether there is a difference in the influence of religious beliefs and affiliation on the sense of coherence between young people from a secular country (such as Germany) and a Catholic country (such as Poland). To empirically capture the sense of coherence a surevy on life orientation was used. Under the concept of „Religeous Beliefs“ it examinded religious convictions, organized and non-organized religious activities. The random sample included 2266 students from Germany and Poland. The participants had Protestant, Catholic, and Buddhist religious affiliations, as well as no religious affiliation. At the individual level, where sense of cohernece was only examined in relation to indicators of religious beliefs, having a religious conviction shows positive effects on students’ sense of coherence. However, its relevance is country-specific. Going to church and being affiliated with a religion has a stronger influence on Polish students’ sense of coherence than on German students.